What have human experimental overfeeding studies taught us about adipose tissue expansion and susceptibility to obesity and metabolic complications? - Cuthbertson, D; Steele, T; Wilding, J; Halford, J; Harrold, J; Hamer, M; Karpe, F (Nature Publishing Group, 2017)
Overfeeding experiments, in which we impose short-term positive energy balance, help unravel the cellular, physiological and behavioural adaptations to nutrient excess. These studies mimic longer-term mismatched energy expenditure and intake. There is considerable inter-individual heterogeneity in the magnitude of weight gain when exposed to similar relative caloric excess reflecting variable activation of compensatory adaptive mechanisms. Significantly, given similar relative weight gain, individuals maybe protected from/predisposed to metabolic complications (insulin resistance, dyslipidaemia, hypertension), non-alcoholic fatty liver disease and cardiovascular disease. Similar mechanistic considerations underpinning the heterogeneity of overfeeding responses are pertinent in understanding emerging metabolic phenotypes e.g. metabolically unhealthy normal weight and metabolically healthy obesity. Intrinsic and extrinsic factors modulate individuals‟ overfeeding response: intrinsic factors include genetic/ethnic background, baseline metabolic health and regional fat distribution; extrinsic factors include macronutrient (fat vs. carbohydrate) content, fat/carbohydrate composition and overfeeding pattern (larger portions vs. snacks). Subcutaneous adipose tissue (SAT) analysis, coupled with metabolic assessment, with overfeeding have revealed how SAT remodels to accommodate excess nutrients. Healthy remodeling involves adipocyte hyperplasia; dysfunctional remodeling involves hypertrophy inducing inflammation and insulin resistance. Biological responses of SAT also govern the extent of ectopic (visceral/liver) fat deposition. Body composition analysis by DEXA/MRI have determined the relative expansion of SAT (including abdominal/gluteofemoral SAT) versus ectopic fat with overfeeding. Such studies have contributed to the adipose expandability hypothesis whereby SAT has a finite capacity to expand (governed by intrinsic biological characteristics) and once capacity is exceeded ectopic fat deposition occurs. The potential for SAT expandability confers protection from/predisposes to the adverse metabolic responses to over-feeding. The concept of a personal fat threshold suggests a large inter-individual variation in SAT capacity with ectopic fat/metabolic decompensation once one's own threshold is exceeded. This review summarises insight gained from overfeeding studies regarding susceptibility to obesity and related complications with nutrient excess.